Puertollano: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A vehicle is a kind of transportation that we can use to deliver goods, materials, and livestock.But, as the years went by, automobile vehicles improved and continuously grew; this is one ofthe reasons why the Philippines is facing road traffic congestion. That’s why one of thesolutions of the government is to put traffic enforcers in every city, barangay, municipality, andprovince who could help make the road much more passable by organizing the properalignment of vehicles and making it less congested than before. The traffic enforcers are alsoresponsible for the flow of vehicles on the highway of Novaliches Quezon City. The LGUassigned traffic enforcers to lessen the traffic in this area..The study found that the presence of traffic enforcers had a positive impact on citing trafficviolations, which is crucial for maintaining trust in law enforcement and governmentinstitutions. Effective traffic violation citation programs can promote road safety and reducerepeated traffic offenses. The study also evaluated the positive impact of traffic enforcers inguiding motorists, which was the most strongly agreed upon by the respondents. Trafficenforcers provided security and guidance, and their support was effective in promoting roadsafety and reducing accidents. However, the respondents were less strongly agreeable withthe effectiveness of traffic enforcers in managing traffic during major events or emergenciesand guiding motorists to safe and alternate routes. In terms of aiding pedestrians, thepresence of traffic enforcers ensured the safe and efficient use of the roads by both motoristsand pedestrians. Traffic enforcers were effective in directing traffic, helping pedestriansnavigate busy intersections, and enhancing pedestrian safety. The data indicated that therespondents strongly agreed on the crucial role of traffic enforcers in aiding pedestrian safetyand promoting positive traffic development in Barangay Bagbag, Novaliches, Quezon City.
Keywords: Criminology